Accumulated exposure to rural areas of residence over the life course is associated with overweight and obesity in adulthood: a 25-year prospective cohort study - Patterson, K; Gall, S; Venn, A; Otahal, P; Blizzard, L; Dwyer, T; Cleland, V (Elsevier, 2017)
This prospective cohort study investigated whether body mass index (BMI) and weight status in mid-adulthood were predicted by trajectories of urban-rural residence from childhood to adulthood.Participants aged 7-15 years in 1985 (n = 8498) were followed up in 2004-2006 (n = 3999, aged 26-36 years) and 2009-2011 (n = 3049, aged 31-41 years). Area of residence (AOR) was classified as urban or rural at each time point. BMI and/or weight status was calculated from self-reported weight and height (2009-2011). We tested which of three life-course models ("accumulation," "sensitive period," "mobility") best explained the AOR-BMI and/or weight status association using a novel life-course modeling framework.Accumulation and sensitive period models best described the effect of AOR on mid-adulthood BMI and weight status. Those with greater accumulated exposure to rural areas had a higher BMI (β = 0.29 kg/m2 per time in a rural area, P = .005) and were more likely obese (relative risk = 1.13 per time in a rural area, P = .002). Living in rural areas at ages 26-30 years was also associated with a higher BMI and obesity in mid-adulthood.Greater cumulative exposure to rurality and exposure during the "sensitive period" of young adulthood is associated with obesity in middle-aged adults. This study highlights the important contribution of context to the development of obesity over the life course.